ANALYSIS OF THE USE OF PROJECT MANAGEMENT TOOLS BY UKRAINIANCOMPANIES - POZNIAKOVSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the features of the creation of civil society institutions (organisations). In Ukraine, accounting for income and expenses of civil society organizations is determined by their non-profit status. The income of civil, charitable, other, non-profit organizations is considered as target income, non-target income, passive and other income. When making expenses, CSOs adhere to the requirements - targeting the implementation of the goal and areas of activity in accordance with the constituent documents and ensuring their target and targeted nature. The features of the creation and functioning of CSOs are not taken into account. CSOs, by their designation, perform tasks that the state cannot cope with due to certain circumstances (in particular, during martial law, other emergencies, etc.), or solve special tasks of a public (social) nature, such as ensuring the interests of certain groups of the population in the territory of their homes, etc. The need to take into account the main functions of civil society institutions when reflecting information about their activities in accounting and financial reporting has been established. The definition of the main accounting objects of civil society institutions is analyzed based on the criterion of using future economic benefits or potential (public) benefits from the provision of public services. It is proposed to classify the income and expenses of public organisations into those received (incurred) from ordinary activities and those that arose (incurred) from unusual (extraordinary) events. The detailing of income and expenses characteristic of the sphere of public activities is considered. The relevance of disclosure by social institutions in accounting and reporting of information about unusual (extraordinary) events is proven in modern conditions of uncertainty and security threats. The unusualness of an event should be based on signs of uncertainty of its occurrence and negative consequences that affect the continuation of the subject’s usual activities. The use of appropriate accounts (sub-accounts) for accounting for income and expenses of civil society institutions is justified. The accounting policy should ensure that the organization complies with the correspondence and comparability of income and expenses incurred for certain projects, charitable purposes (areas) or for the management (maintenance) of the organization.